Third‐party bone marrow–derived mesenchymal stromal cell infusion before liver transplantation: A randomized controlled trial. Issue 8 (22nd February 2021) - Casiraghi, Federica; Perico, Norberto; Podestà, Manuel A.; Todeschini, Marta; Zambelli, Marco; Colledan, Michele; Camagni, Stefania; Fagiuoli, Stefano; Pinna, Antonio D.; Cescon, Matteo; Bertuzzo, Valentina; Maroni, Lorenzo; et al.
Abstract: Mesenchymal stromal cells (MSC) have emerged as a promising therapy to minimize the immunosuppressive regimen or induce tolerance in solid organ transplantation. In this randomized open‐label phase Ib/IIa clinical trial, 20 liver transplant patients were randomly allocated (1:1) to receive a single pretransplant intravenous infusion of third‐party bone marrow–derived MSC or standard of care alone. The primary endpoint was the safety profile of MSC administration during the 1‐year follow‐up. In all, 19 patients completed the study, and none of those who received MSC experienced infusion‐related complications. The incidence of serious and non‐serious adverse events was similar in the two groups. Circulating Treg/memory Treg and tolerant NK subset of CD56 bright NK cells increased slightly over baseline, albeit not to a statistically significant extent, in MSC‐treated patients but not in the control group. Graft function and survival, as well as histologic parameters and intragraft expression of tolerance‐associated transcripts in 1‐year protocol biopsies were similar in the two groups. In conclusion, pretransplant MSC infusion in liver transplant recipients was safe and induced mild positive changes in immunoregulatory T and NK cells in the peripheral blood. This study opens the way for a trial on possible tolerogenic efficacy of MSC in liver transplantation. ClinicalTrials.gov identifier: NCT02260375. Abstract : This randomized controlled trial shows that pretransplant infusion of third‐party bone marrow–derived mesenchymal stromal cells in liver transplant recipients is safe and induces modest increases in circulating regulatory T and natural killer cells.